Analysis of the P1 promoter in response to UV-B radiation in allelic variants of high-altitude maize - Rius, Sebastián Pablo (BioMed Central, 2012)
BACKGROUND: Plants living at high altitudes are typically exposed to elevated UV-B radiation, and harbor mechanisms to prevent the induced damage, such as the accumulation of UV-absorbing compounds. The maize R2R3-MYB transcription factor P1 controls the accumulation of several UV-B absorbing phenolics by activating a subset of flavonoid biosynthetic genes in leaves of maize landraces adapted to high altitudes. RESULTS: Here, we studied the UV-B regulation of P1 in maize leaves of high altitude landraces, and we investigated how UV-B regulates P1binding to the CHS promoter in both low and high altitude lines. In addition, we analyzed whether the expansion in the P1 expression domain between these maize landraces and inbred lines is associated to changes in the molecular structure of the proximal promoter, distal enhancer and first intron of P1. Finally, using transient expression experiments in protoplasts from various maize genotypes, we investigated whether the different expression patterns of P1 in the high altitude landraces could be attributed to trans- or cis-acting elements. CONCLUSIONS: Together, our results demonstrate that, although differences in cis-acting elements exist between the different lines under study, the different patterns of P1 expression are largely a consequence of effects in trans.